Total synthesis of (–)-6,7-dideoxysqualestatin H5 by carbonyl ylide cycloaddition and cross–electrophile coupling - Fegheh-Hassanpour, Y (2018)
The work presented in this thesis focuses on the total synthesis of (–)-6,7- Dideoxysqualestatin H5. Particular emphasis was the development of a cross– coupling strategy for direct delivery of the side chain towards the end of the synthesis. Various methods investigated to perform the key Csp3–Csp2 coupling initially led to the Fu variant of the Negishi coupling at elevated temperatures and subsequent cross– electrophile coupling at rt. Key features of the asymmetric synthesis of (–)-6,7- dideoxysqualestatin H5, include: (1) highly diastereoselective n-alkylation of a tartrate acetonide enolate and subsequent oxidation-hydrolysis to provide an asymmetric entry to a β-hydroxy-α-ketoester motif; (2) facilitation of Rh(II)-catalysed cyclic carbonyl ylide formation-cycloaddition by cogeneration of keto and diazo functionality through ozonolysis of an unsaturated hydrazone; and (3) stereoretentive Ni-catalysed Csp3–Csp2 cross–electrophile coupling between tricarboxylate core and unsaturated side-chain to complete the natural product. Following completion of the natural product, further work was carried out on the ozonolysis of unsaturated tosylhydrazones as a direct approach to diazocarbonyls. The scope and limitations of reacting unsaturated tosylhydrazones with O3 followed by Et3N for the generation of 1,4- and 1,5-diazocarbonyl systems were explored. Tosylhydrazones, from tosylhydrazide condensation with readily available δ- and ε- unsaturated α-ketoesters, led in the former case to a 2-pyrazoline whereas the latter cases led to α-diazo-ε-ketoesters, although a terminal alkene produced a tetrahydropyridazinol. Tosylhydrazones from cyclic enones also allowed access to 1,4- and 1,5-diazocarbonyl systems using the ozonolysis–Et3N strategy.